Small Scale Experiment: Thermal Performance Comparison Between Fiber-Cement Roof and Photovoltaic Roof In Malang, Indonesia - Bonifacius, Nurhamdoko; Ekasiwi, Sri Nastiti Nugrahani (Makara Journal of Technology, 2012)
Irradiation on the surface of photovoltaic module heats up the photovoltaic module itself and the room underneath the roof of integrated photovoltaic building in the tropics area. Room heating reduces thermal condition and photovoltaic module surface heating reduces its performance in generating electricity. This paper discusses an experiment of measuring the surface temperature of photovoltaic modules and fiber-cement roof surface as a comparison. This experiment also measures the impact of rising temperatures in each space underneath. It used small-scale mock-ups exposed to direct sunlight. The result of the experiment shows that photovoltaic roof surface temperature is lower than fiber-cement roof temperature. The temperature of room under photovoltaic roof is also lower than the one under fibercement roof. Empirical calculation shows that loss of electrical power found is only up to 1.7%.